2019
DOI: 10.1177/0960327119843583
|View full text |Cite
|
Sign up to set email alerts
|

Dibutyl phthalate-induced activation of ROS and ERK1/2 causes hepatic and renal damage in Kunming mice

Abstract: Dibutyl phthalate (DBP), a ubiquitous environmental contaminant, has been reported to be involved in hepatic and renal tissue damage. However, the role of DBP in oxidative stress and in extracellular signal-regulated kinase (ERK1/2) pathways remains unclear. To investigate the underlying mechanism, Kunming (KM) mice received daily doses of combinations of 50 mg/kg DBP, 50 mg/kg vitamin E (VitE), and 1 mg/kg PD98059 for 28 consecutive days. Any changes in reactive oxygen species (ROS) and malondialdehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 34 publications
2
25
0
Order By: Relevance
“…Phthalate esters are ubiquitously present in several consumer products and are known to induce oxidative stress in experimental models [ 22 , 23 ]. This effect has been associated with tissue atrophy, impaired tissue antioxidant defence and nephrotoxicity in different experimental models [ [24] , [25] , [26] , [27] , [28] ].…”
Section: Introductionmentioning
confidence: 99%
“…Phthalate esters are ubiquitously present in several consumer products and are known to induce oxidative stress in experimental models [ 22 , 23 ]. This effect has been associated with tissue atrophy, impaired tissue antioxidant defence and nephrotoxicity in different experimental models [ [24] , [25] , [26] , [27] , [28] ].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have suggested that, when present in adequate amounts, ROS act as signaling molecules by participating in signal transduction pathways and can induce changes in enzyme activity, apoptosis, and necrosis. Finally, this leads to pathological changes and organ dysfunction [ 35 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar changes of the same parameters have been observed in animals (earthworms, Danio rerio , mice, rats). These examples may indicate that these substances produce oxidative stress in various organisms [ 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…It produces synergistic or combined responses to different extracellular stimuli and is closely related to cell proliferation, differentiation, apoptosis, and other activities (Finkel, 2011). The liver and kidneys can eliminate excess ROS through their own antioxidants and antioxidant enzymes, so the body's oxidants and antioxidants are dynamically balanced under normal conditions (Cheng et al, 2019;Valko et al, 2007). However, when some exogenous chemicals act excessively, this may lead to the rapid production of ROS and an imbalance between oxidation and anti-oxidation in cells or tissues.…”
Section: Discussionmentioning
confidence: 99%